International Management / Second Edition - Hodgetts Richard M; Luthans Fred (Mcgraw Hill, Inc, 1994)
Preface, An Overall Perspective of International Management, Worldwide Developments, Foundations for International Management, The Cultural Context for International Management, Managing Across Cultures, Strategies and Functions of Managing International Organizations, Strategic Planning, Managing Political Risk and Negotiations, Organizing International Operations, Decision Making and Controlling, Functions of International Human Resources Management, Personnel Selection and Repatriation, Training and Organization Development, Labor Relations and Industrial Democracy, Managing People in International Organizations, Communication, Motivating Human Resources, Leading Human Resources, International Management Horizons, Ethics and Social Responsibility, Future of International Management, References, Glossary, Index.
Preface, An Overall Perspective of International Management, Worldwide Developments, Foundations for International Management, The Cultural Context for International Management, Managing Across Cultures, Strategies and Functions of Managing International Organizations, Strategic Planning, Managing Political Risk and Negotiations, Organizing International Operations, Decision Making and Controlling, Functions of International Human Resources Management, Personnel Selection and Repatriation, Training and Organization Development, Labor Relations and Industrial Democracy, Managing People in International Organizations, Communication, Motivating Human Resources, Leading Human Resources, International Management Horizons, Ethics and Social Responsibility, Future of International Management, References, Glossary, Index.